Important Metabolic Pathways and Biological Processes Expressed by Chicken Cecal Microbiota - Polansky, Ondrej; Sekelova, Zuzana; Faldynova, Marcela; Sebkova, Alena; Sisak, Frantisek; Rychlik, Ivan (Applied and environmental microbiology, 2015)
The gut microbiota plays important roles in its host. However, how each microbiota member contributes to the behavior of the whole population is not known. In this study, we therefore determined protein expression in the cecal microbiota in chickens of selected ages and in 7-day-old chickens inoculated with different cecal extracts on the day of hatching. Campylobacter, Helicobacter, Mucispirillum, and Megamonas overgrew in the ceca of 7-day-old chickens inoculated with cecal extracts from donor hens. Firmicutes were characterized by ABC and phosphotransferase system (PTS) transporters, extensive acyl coenzyme A (acyl-CoA) metabolism, and expression of l-fucose isomerase. Anaerostipes, Anaerotruncus, Pseudoflavonifractor, Dorea, Blautia, and Subdoligranulum expressed spore proteins. Firmicutes (Faecalibacterium, Butyrivibrio, Megasphaera, Subdoligranulum, Oscillibacter, Anaerostipes, and Anaerotruncus) expressed enzymes required for butyrate production. Megamonas, Phascolarctobacterium, and Blautia (exceptions from the phylum Firmicutes) and all Bacteroidetes expressed enzymes for propionate production pathways. Representatives of Bacteroidetes also expressed xylose isomerase, enzymes required for polysaccharide degradation, and ExbBD, TonB, and outer membrane receptors likely to be involved in oligosaccharide transport. Based on our data, Anaerostipes, Anaerotruncus, and Subdoligranulum might be optimal probiotic strains, since these represent spore-forming butyrate producers. However, certain care should be taken during microbiota transplantation because the microbiota may behave differently in the intestinal tract of a recipient depending on how well the existing communities are established.
Keywords: společenstvo; kur domácí; Animals; Metabolic Networks and Pathways; metabolické sítě a dráhy; zvířata; Biota; cékum; Cecum; střevní mikroflóra; Chickens; Gene Expression Profiling; stanovení celkové genové exprese; Gastrointestinal Microbiome